Transformation by different oncogenes relies on specific metabolic adaptations. Issue 19 (1st October 2016) - Peruzzo, Paolo; Comelli, Marina; Di Giorgio, Eros; Franforte, Elisa; Mavelli, Irene; Brancolini, Claudio
ABSTRACT: Metabolic adaptations are emerging as common traits of cancer cells and tumor progression. In vitro transformation of NIH 3T3 cells allows the analysis of the metabolic changes triggered by a single oncogene. In this work, we have compared the metabolic changes induced by H-RAS and by the nuclear resident mutant of histone deacetylase 4 (HDAC4). RAS-transformed cells exhibit a dominant aerobic glycolytic phenotype characterized by up-regulation of glycolytic enzymes, reduced oxygen consumption and a defect in complex I activity. In this model of transformation, glycolysis is strictly required for sustaining the ATP levels and the robust cellular proliferation. By contrast, in HDAC4/TM transformed cells, glycolysis is only modestly up-regulated, lactate secretion is not augmented and, instead, mitochondrial oxygen consumption is increased. Our results demonstrate that cellular transformation can be accomplished through different metabolic adaptations and HDAC4/TM cells can represent a useful model to investigate oncogene-driven metabolic changes besides the Warburg effect.